The effects of salt and drought stress on phenolic accumulation in greenhouse-grown Hypericum pruinatum - Caliskan, Omer; Radusiene, Jolita; Temizel, Kadir Ersin; Staunis, Zydrunas; Cirak, Cuneyt; Kurt, Dursun; Odabas, Mehmet Serhat (Italian Journal of Agronomy, 2017)
Hypericum pruinatum is a medicinal herb containing several bioactive compounds with important pharmacological activity. In this study, we investigated the effects of the salt (0.03 - control, 1, 2.5, 4 and 8 dS m–1 of MgSO4, CaCl2 and NaCl salts) and drought stress (80, 100 and 120% of required water) on the content of phenolic compounds, namely chlorogenic acid, rutin, hyperoside, isoquercetine, quercitrine and quercetine in greenhouse grown plantlets. In general, the salt stress especially in elevating doses increased the levels of all of the compounds analysed, whereas drought stress did not cause a significant chance in chemical content of the plantlets. The present results indicated that abiotic stress factors, particularly salinity, have a marked influence on the content of phenolic constituents in H. pruinatum and it is a salt tolerant species. The results also indicated that phenolic compounds play significant physiological role in salinity tolerance.